2003
DOI: 10.1007/s00167-003-0385-4
|View full text |Cite
|
Sign up to set email alerts
|

Positive culture in allograft ACL-reconstruction: what to do?

Abstract: The transmission of disease or infection from the donor to the recipient is always a risk with the use of allografts. We carried out a research study on the behavioural pattern of implanted allografts, which were initially stored in perfect conditions (all cultures being negative) but later presented positive cultures at the implantation stage. Because there is no information available on how to deal with this type of situation, our aim was to set guidelines on the course of action which would be required in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 21 publications
(27 reference statements)
2
18
0
Order By: Relevance
“…The culture-positive organisms in our study are similar to the organisms in the studies by Deijkers et al 7 and Diaz-de-Rada et al, 8 which may suggest contamination during procurement or processing. In our study, the cultures became positive 4 to 5 days postoperatively, at which point patients were not receiving antibiotics.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The culture-positive organisms in our study are similar to the organisms in the studies by Deijkers et al 7 and Diaz-de-Rada et al, 8 which may suggest contamination during procurement or processing. In our study, the cultures became positive 4 to 5 days postoperatively, at which point patients were not receiving antibiotics.…”
Section: Resultssupporting
confidence: 89%
“…Of note, there was a low virulence bacterial contamination rate of 50% and a high virulence rate of 3%. Diaz-de-Rada et al 8 reported a 13% culture-positive rate in BPTB allografts used in ACL reconstructions and recommended the use of prophylactic antibiotics for 2 weeks. The study reported no clinical infections in their series, despite the high rate of positive cultures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Diaz-de-Rada et al had 24 positive cultures from 181 allograft implantations analyzed; no patients showed clinical infection during follow-up. 22 Hence, culture-positive evidence of allograft contamination did not correlate with infectious complications. 14 …”
Section: Allograft Versus Autograft: Incidence Of Sepsismentioning
confidence: 97%
“…Studies that met the inclusion criteria included (1) prospective randomized controlled trials, (2) prospective and retrospective nonrandomized trials, and (3) case series.…”
Section: Methodsmentioning
confidence: 99%